PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN PERCEIVED RISK UNTUK MENGIDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU BELANJA ONLINE DI KALIMANTAN - Sajieda Fuad; Marijati Sangen; Siti Aliyati Albushari (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
Internet in Indonesia has a very diverse usage in various aspects of life. One of them is that it can be used in economic transaction that is buying and selling online or better known as e-commerce (electronic commerce). This study aims to factors are perceived usefulness, perceived ease of use, perceived risk, attitude toward using, and behavioral intention. This research was conducted in Kalimantan. The samples of the research were determined using non-probability sampling method in the form of purposive sampling with the requirements: the samples were at least 18 years of age and they had made purchases of goods or services through online shopping site of B2C e- commerce at least twice. The research method used was survey method through primary data collection by distributing online questionnaires through Google Docs. Data analysis was done by SEM (Structural Equation Modeling) with AMOS (Analysis of Moment Structure) 21.0 software. The result showed that perceived usefulness and perceived ease of use had positive and significant effect on attitude toward using. However, perceived risk did not have a negative and insignificant effect on attitude toward using. Perceived ease of use had a positive and significant effect on perceived usefulness. Perceived usefulness and attitude toward using positively and significantly influenced the behavioral intention of online shopping in Kalimantan. Perceived ease of use was the most dominant variable giving a direct influence on perceived usefulness, perceived usefulness gave the most dominant indirect influence on behavioral intention